L.M. Montgomery and the Matter of Nature(s). - Bode, Rita, 1950-; Mitchell, Jean, 1953- (McGill-Queen's University Press, 2018)
A critical study of L.M. Montgomery's relationship to the material world and the revealing interconnections between nature and culture.